A previously unrecorded reverse for Constantine I - Clark, Victor (KOINON: The International Journal of Classical Numismatic Studies, 2018)
The coin pictured above is a previously unknown reverse type for Constantine I. For people interested in Constantine and his coinage, this is an exciting discovery. New types do not appear very often and, surprisingly, this example turned up on eBay. This coin was sold as part of an otherwise unremarkable group of coins on eBay in January of 2017.